Iranian Migrants’ Perceptions of Turkish and Iranian Culture: A Comparative Analysis with ZMET Technique - Berfin Varışlı; Fatemeh Sarvari Kohnehshahri; Mikail Batu (Türkiye İletişim Araştırmaları Dergisi)
This study aims to determine the perceptions of culture and communication in the social life of Iran and Türkiye. In the study, the prominent aspects of how Iranian migrants experience the culture and communication in the social life were examined. Furthermore, it was endeavored to ascertain the most important issues in Turkish and Iranian culture for Iranian migrants. In this context, Iranian migrants who reside in Türkiye were reached by using Snowball Sampling method, and Zaltman’s ZMET Technique was used in the study. According to this technique, in-depth interviews were made with 10 Iranian migrants who reside in Türkiye. The contents of the interviews were transferred to a virtual environment as text, and specific codes were determined via content analysis. As a result of this analysis, a consensus map was created. Consequently, it was observed that Iranian migrants associated Iranian culture with the Nowruz festival, family, Iranian dishes and desserts, historical symbols, and religious symbols and they described Turkish culture through Atatürk, the Turkish flag, family, city, and the social life. The participants mentioned that Iran is in a global war and therefore, they depicted the country mostly in the color red. The cultural codes and the colors red, blue, green, and beige were emphasized for Türkiye.